Confirmatory analysis of the 13‐MD and ranking of its meta‐dimensions and items - Moustapha Touré; Thomas G. Poder (Wiley, 2024)
Abstract Background The 13‐MD is a new generic instrument developed to measure general health‐related quality of life (GHRQoL). This instrument considers all aspects of health (i.e., physical, mental, and social) in a balanced way. A previous study led to minor changes in the original version of the 13‐MD. The objective of this study was to confirm the validity of the modified 13‐MD. Methods Validity was assessed with recent data from the general population of Quebec, Canada. The meta‐dimensions and items composing the 13‐MD were also subjected to a ranking procedure, which allowed to determine the most important aspects for respondents. Results A total of 1337 French‐speaking participants were recruited with 1099 completing the 13‐MD for validation purposes and 1084 completing the ranking procedure. The 13‐MD showed very satisfactory results and confirmed to be a valid instrument. The ranking of the meta‐dimensions revealed that "Well‐being" received the most points, followed by "Sleep and energy" and "Body functioning." Conclusion These results will be very useful in the continuous improvement of the 13‐MD, ultimately leading to the valuation stage (i.e., development of a value set).